Effect of (3‐aminopropyl)triethoxysilane coupling agent on characteristics and mechanical properties of polylactic acid/jute fiber biocomposite. Issue 1 (25th February 2019) - Huynh, Mai Duc; Trung, Tran Huu; Thai, Nguyen Thi; Van Cong, Do; Tung, Nguyen Huy; Giang, Nguyen Vu
Abstract: Biocomposites based on polylactic acid (PLA) and jute fiber (JF) (90/10 wt.%/wt.%) were prepared by melt mixing method in the internal Poly Haake mixer. Before preparing PLA/JF biocomposites, JF was cut into the shorter fiber with 1‐2 mm in length and was modified by 1, 5 and 10 wt.% of (3‐aminopropyl)triethoxysilane (APTES). Fourier transform infrared (FTIR) spectroscopy was conducted to evaluate the presence of APTES on the JF surface. The mechanical properties of PLA/JF biocomposites including tensile strength, Young's modulus and impact strength were investigated. It is found that APTES improved remarkably the mechanical properties and reached the maximum values for sample using 5 wt.% APTES. The composites using modified JF showed the higher thermal stability in comparison to the unmodified sample. SEM micrographs of the fractured surface area exhibited the better adhesion between JF and PLA matrix after modification.